Cycles of meaning-making crystallization in the WeValue InSitu process as clear contributions towards transformative learning. (1st July 2021) - Odii, Benita C.; Huang, Yanyan; Bouvrie, Nicole des; Harder, Marie K.
Abstract: Transformative learning is highly sought by practitioners and academics in sustainable development, education for sustainable development, and adult education, because it involves shifts in perspectives which can potentially underpin significant changes in worldviews and ways of learning. A practice-based design process for crystallizing local shared values, called WeValue InSitu, is already reported to regularly produce transformative learning (TL), but its lack of discipline- or theory-based origins means there are currently no ways to formalise its mechanisms. There is thus a need to conceptualize the sub-processes within it in order to provide a theoretical underpinning, and to extract key contributions to the production of transformative learning (TL). Here, Polanyi's fine-toothed micro-processes are used to analyse discourses from transcripts of a WeValue InSitu event to reveal patterns of meaning-making and meaning-checking cycles. Also identified are key facilitator actions of: redirecting, challenging, refocusing, reflecting back, and disentangling concepts. These findings allow a self-consistent conceptualization of the WeValue InSitu sub-processes and thus a formal methodology. Furthermore, these will lead to more widespread transferability and scaling-up of WeValue InSitu in the field, to meet demand for its known uses e.g. in climate change adaptation planning, sustainability assessments, and education. The reconceptualized sub-processes also contribute to wider TL research, since it will enable reliable TL production to replace fortuitous case studies. With that, there can now be a new TL research agenda for systematic studies e.g. of TL learning mechanisms and contextual influences on TL. Highlights: WeValue InSitu's Transformative Learning (TL) sub-processes are revealed. TL sub-processes are shown to be collective meaning-making, -checking cycles. Facilitator techniques which are key, are identified specifically. Design steps are formally reconceptualized and articulated for use in training. This conceptualization opens doors to accelerated theory-building in TL.